Exploring the chemical properties and microstructural characterisations of hybrid asphalt binders for enhanced performance - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Khairil Azman, Masri; Saptaji, Kushendarsyah; Dulaimi, Anmar (Springer Nature, 2024)
Approximately 3 billion metric tonnes of garbage involving industrial and agricultural waste is expected to be generated by 2030, posing a significant environmental hazard. Notably, recycling or reusing asphalt modification components (palm oil fuel ash (POFA), garnet waste, and sawdust) in pavement construction encounter ongoing challenges. This study comprehensively assessed the chemical characteristics and microstructure analysis of individual wastes and various hybrid asphalt binder and mixtures incorporated with these components. The mixture consisted of asphalt grade 60/70 blended with varying amounts (0%, 3%, 6%, and 9%) of POFA, garnet waste, and sawdust. Fourier transform infrared spectroscopy (FTIR), X-ray fluorescence (XRF), and X-ray diffraction (XRD) analyses were also employed to examine the chemical compositions of the raw waste materials. Meanwhile, the microstructure properties of various hybrid asphalt binder mixtures were analysed utilising Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). Consequently, this study presented that the correlation between the 6% POFA, 6% garnet waste, and 6% sawdust substantially impacted the chemical composition and morphology of the mixture. The findings of this study demonstrated that including POFA, garnet waste, and sawdust in a hybrid asphalt binder and mixture could enhance performance and engineering properties.